Comparison of six risk scores for stroke-associated pneumonia in patients with acute ischemic stroke: A systematic review and Bayesian network meta-analysis - Zhang, Xuemin; Xiao, Lu; Niu, Liqing; Tian, Yongchao; Chen, Kuang (Frontiers in Medicine, 2022)
Background Stroke-associated pneumonia (SAP) is one of the major causes of death after suffering a stroke. Several scoring systems have been developed for the early prediction of SAP. However, it is unclear which scoring system is more suitable as a risk prediction tool. We performed this bayesian network meta-analysis to compare the prediction accuracy of these scoring systems. Methods Seven databases were searched from their inception up to April 8, 2022. The risk of bias assessment of included study was evaluated by the QUADAS-C tool. Then, a Bayesian network meta-analysis (NMA) was performed by R 4.1.3 and STATA 17.0 software. The surface under the cumulative ranking curve (SUCRA) probability values were applied to rank the examined scoring systems. Results A total of 20 cohort studies involving 42236 participants were included in this analysis. The results of the NMA showed that AIS-APS had excellent performance in prediction accuracy for SAP than Chumbler (MD=0.030, 95%CI: 0.004,0.054), A2DS2(MD=0.041, 95% CI: 0.023,0.059), ISAN (MD=0.045, 95% CI: 0.022,0.069), Kwon (MD=0.077, 95% CI: 0.055,0.099) and PANTHERIS (MD=0.082, 95% CI: 0.049,0.114). Based on SUCRA values, AIS-APS (SUCRA: 99.8%) ranked the highest. Conclusion In conclusion, the study found that the AIS-APS is a validated clinical tool for predicting SAP after the onset of acute ischemic stroke.